Pendidikan Kristen Dalam Menghadapi Pembelajaran Daring Sinkron dan Asinkron - Filgod, Dejan; Tangkin, Wiyun Philipus (Sekolah Tinggi Teologi Kanaan Nusantara, 2022)
Education should be implemented online whether synchronously and asynchronously because of Covid-19 pandemic since the end of 2019. According to the survey from KPAI on 1.700 students, there are problems are occurred during the implementation of online learning. Problems that occurred throughout the online learning caused by several aspects such as facility, the teacher, and the student. Significantly, education should be conducted consecutively because it is a long-life process. This paper serves to investigate responses that Christian education should apply to face current issues. Literature review based on the truth of the Scripture as the source of truth is used in writing this paper. An understanding of the definition and purpose of Christian education will assist each individual who is involved in education. For that reason, personal identity as a concrete embodiment of God’s Image which is marred with sin yet redeemed by Christ has implications for every action that is committed by each person. Last but not least, live in vigilance based on the Scripture’s truth will prepare the teacher to be responsive to face every problem. Thus, every person in Christian education should have that understanding. Therefore, Christian education will have a proper response in facing problems throughout its implementations in online learning during the Covid-19 pandemic and other kinds of problems.